Hospital Consultation From Outpatient Clinicians for Medically Complex Children: A Randomized Clinical Trial - Mosquera, Ricardo A. (JAMA Pediatr, 2020)
IMPORTANCE: Children with medical complexity (CMC) frequently experience fragmented care. We have demonstrated that outpatient comprehensive care (CC) reduces serious illnesses, hospitalizations, and costs for high-risk CMC. Yet continuity of care for CMC is often disrupted with emergency department (ED) visits and hospitalizations. OBJECTIVE: To evaluate a hospital consultation (HC) service for CMC from their outpatient CC clinicians. DESIGN, SETTING, AND PARTICIPANTS: Randomized quality improvement trial at the University of Texas Health Science Center at Houston with an outpatient CC clinic and tertiary pediatric hospital (Children’s Memorial Hermann Hospital). Participants included high-risk CMC (≥2 hospitalizations or ≥1 pediatric intensive care unit [PICU] admission in the year before enrolling in our clinic) receiving CC. Data were analyzed between January 11, 2018, and December 20, 2019. INTERVENTIONS: The HC included serial discussions between CC clinicians, ED physicians, and hospitalists addressing need for admission, inpatient treatment, and transition back to outpatient care. Usual hospital care (UHC) involved routine pediatric hospitalist care. MAIN OUTCOMES AND MEASURES: Total hospital days (primary outcome), PICU days, hospitalizations, and health system costs in skeptical bayesian analyses (using a prior probability assuming no benefit). RESULTS: From October 3, 2016, through October 2, 2017, 342 CMC were randomized to either HC (n = 167) or UHC (n = 175) before meeting the predefined bayesian stopping guideline (>80% probability of reduced hospital days). In intention-to-treat analyses, the probability that HC reduced total hospital days was 91% (2.72 vs 6.01 per child-year; bayesian rate ratio [RR], 0.61; 95% credible interval [CrI], 0.30-1.26). The probability of a reduction with HC vs UHC was 98% for hospitalizations (0.60 vs 0.93 per child-year; RR, 0.68; 95% CrI, 0.48-0.97), 89% for PICU days (0.77 vs 1.89 per child-year; RR, 0.59; 95% CrI, 0.26-1.38), and 94% for mean total health system costs ($24 928 vs $42 276 per child-year; cost ratio, 0.67; 95% CrI, 0.41-1.10). In secondary analysis using a bayesian prior centered at RR of 0.78, reflecting the opinion of 7 experts knowledgeable about CMC, the probability that HC reduced hospital days was 96%. CONCLUSIONS AND RELEVANCE: Among CMC receiving comprehensive outpatient care, an HC service from outpatient clinicians likely reduced total hospital days, hospitalizations, PICU days, other outcomes, and health system costs. Additional trials of an HC service from outpatient CC clinicians are needed for CMC in other centers. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02870387